FINITE p-GROUPS IN WHICH NORMAL CLOSURES FOR EVERY NONNORMAL SUBGROUPS ARE MINIMAL NONABELIAN - Yu, Dapeng; Chen, Guiyun; Xue, Haibo; Lv, Heng (Italian Journal of Pure and Applied Mathematics, 2015)
The authors study finite p-groups G such that AG is minimal non-abelian for all non-normal subgroup A < G. This topic is Problem 805 posed by Berkovich and Janko in [?]. The authors give the complete classification of such kind of p-groups.